Corruption in the Pharmaceutical Sector Diagnosing the Challenges - Rehan Haider; Asghar Mehdi; Anjum Zehra; Geetha Kumari Das; Zameer Ahmed (PT FORMOSA CENDEKIA GLOBAL, 2024)
Corruption inside the pharmaceutical industry is a pervasive and complicated problem that poses giant challenges to healthcare structures, public welfare, and ethical requirements. This abstract delves into the prognosis of the challenges posed by corruption in the pharmaceutical industry. The pharmaceutical sector performs a vital function in promoting international fitness by growing, generating, and distributing life-saving medicines. However, the arena is plagued by various kinds of corruption, such as bribery, fraud, kickbacks, and undue influence on regulatory procedures. This corruption leads to distorted priorities, compromised drug satisfaction, decreased access to important drug treatments, and expanded healthcare costs. One challenge is the complex web of relationships among pharmaceutical corporations, healthcare professionals, and regulatory governments. These relationships, while regularly critical for understanding trade and innovation, may be exploited for corrupt practices that prioritize income over patient well-being. Furthermore, inadequate regulation and susceptible enforcement mechanisms create an environment where corrupt activities can flourish